Incidence of Lumbosacral Transitional Vertebrae in Patients with Low Back Pain - Ali Raza Shah, Sana Farid Khan, Fahim Khan, Sohail Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The lumbar spine's lumbrosacral transitional vertebrae (LSTV), a structural defect, have been variously linked to low back pain (LBP). Their presence can also lead to an incorrect pre-operative level identification. Objective: To examine the relationship between lumbosacral transitional vertebrae detected on plain radiographs and low back pain in patients. Study Setting: Department of orthopedics, Shifa international hospital, Islamabad Methods: The study design was prospective and descriptive. The study was conducted between July 2021 to December 2021. The radiographs of 100 patients with low back pain who met the inclusion/exclusion criteria were evaluated. The frequency of patients with low back pain and lumbosacral transitional vertebra (LSTV) was calculated using SPSS version 26. For the quantitative data presentation mean and standard deviation was utilized and for qualitative data frequencies were used. P value less than 0.05 was considered significant. Results: In a sample of 100 patients, 40 were men and 60 were women. 45 patients were diagnosed with axial type of lower back pain. The prevalence of LSTV was 27%, with males constituting the majority. No significant difference in the LSTV and Normal spine age distribution intervals was observed except, in the age interval of 51-60 years with a P-Value of <0.001. Conclusion: There is substantial evidence linking lumbosacral transitional vertebrae and low back pain.